Capital market integration and macroeconomic stability - Franziska Bremus; Ruth Stelten (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
After the establishment of the Banking Union, the European Commission is working on measures to foster capital market deepening in Europe. Key goals for a European Capital Markets Union are to provide firms with alternative funding sources to bank credit and to make economies more resilient to local shocks through better international risk sharing. While open capital markets can improve portfolio diversification, growth and welfare, the recent financial crisis was a reminder that capital market integration also carries risks in terms of economic stability. This article summarizes pros and cons of capital market openness and discusses stability implications of different forms of capital market integration.
Keywords: 330